ابلاغ کی ارتقائی تاریخ: سیرتِ طیبہ کی روشنی میں ایک مطالعہ (Al-Qamar, 2025)
This study offers a comprehensive historical and analytical examination of the evolution of communication from ancient times to the contemporary digital age, interpreted through religious, historical, and theoretical perspectives, with particular emphasis on the Seerat-e-Tayyeba. It argues that communication is not a purely modern construct but an intrinsic aspect of human existence, rooted in early human consciousness and divine revelation. Tracing the progression from non-verbal gestures, speech, and writing to printing, electronic media, and artificial intelligence, the article situates modern communication technologies within a broader civilizational continuum. Special attention is given to the prophetic model of communication demonstrated by Prophet Muhammad ﷺ, highlighting principles such as truthfulness, wisdom, ethical responsibility, audience awareness, and contextual relevance. By integrating prehistoric, classical, Islamic, and modern phases of communication, the study presents Seerat-e-Tayyeba as a timeless and holistic communicative framework capable of guiding contemporary media practices amid rapid technological.
Keywords: History of Communication, Seerat-e-Tayyeba, Divine Revelation, Prehistoric and Classical Communication, Islamic Communication Ethics